Application of anthropometric approach in lessening disorders and stress-related issues - Ikubanni, P. P.; Akande, K. A.; Agboola, O. O. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Local weaving is an occupation of making a local type of clothing in the South Western and some part of North-central Nigeria using local methods of weaving. This kind of clothing is called “aso-òkè”. This method is an age-long one, which persist until today. However, due to the shortage of white collar jobs and there is little or no production of clothing materials by the nation’s several textile companies coupled with the desire for the traditional wears as a form of social class, the number of youths involved in this vocation as a means of livelihood has increased considerably over the last few years. In consideration of previous studies, which have reported many health disorders and stress that arises from the uncomfortable sitting positions and unsuitable seats at work, anthropometric data obtained from some of the male local weavers in Ilorin, North-central Nigeria were analyzed. This study was designed to determine the ergonomic suitability of local weavers’ seat and to propose ergonomically viable dimensions that will lessen disorders and pains. A standard dimension of an ergonomic chair that will help ease the disorder and stress-related injuries and illness experienced by these workers was proposed. A total of 100 male local weavers participated in this study. The data were analysed using descriptive statistics of mean, standard deviation, range and percentile. The results showed that there was a significant difference between the former seat being used and the anthropometric variables measured. The proposed dimensions from the study include Seat Height (40.3- 46.2 cm), Seat Breadth (36.5-41.8 cm) and Seat Backrest (49.6-60.2 cm). It was concluded that the seat being used by the local weavers in carrying out their daily work is not ergonomically suitable. Further studies that will include female weavers as well as weavers and other professionals from the South Western part of the country is envisaged. Apart from proposing standard dimension, this study presents several anthropometric data from North Central Nigerians, which could help production companies in the developing and developed world in designing appropriate workstations, worktables, office chairs for use in some part of the country.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 1, 2017, page: 45-55